Alloiococcus otitidis—Cause of Nonspecific Acute Sinusitis: First Case Report and Review of Literature - Tanja Grubić Kezele; Maja Abram; Marina Bubonja-Šonje (Microorganisms, 2022)
Although most sinus infections are viral, potential bacterial pathogens such as Streptococcus pneumoniae, Haemophilus influenza and Moraxella catarrhalis can migrate during a viral respiratory infection from the nasopharynx into the sinus cavity causing sinusitis. Alloiococcus otitidis is a commensal of the external auditory canal and is considered one of the potential middle ear pathogens. Unlike most otopathogens, A. otitidis is rarely found in the nasopharynx of healthy individuals. This difficult-to-culture organism has not previously been described as a causative agent of sinusitis. Here we describe one case of acute sinusitis due to A. otitidis and review previous knowledge of this controversial organism based on recent literature.